1985
DOI: 10.1161/01.str.16.6.940
|View full text |Cite
|
Sign up to set email alerts
|

Internal carotid artery occlusion: clinical and therapeutic implications.

Abstract: SUMMARY Five hundred patients referred to the Cerebrovascular Clinic of the Johannesburg Hospital were examined by a battery of noninvasive tests and angiography. Thirty four occlusions of the internal carotid artery were found in 32 patients. These patients were prospectively evaluated, including clinical examination, analysis of risk factors and subsequent management. This group of patients was followed up for a mean period of 18 months, and the clinical and laboratory findings and follow up data of this gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Wade et al [26] _______ ___________ (bilateral carotid occlusion) Fritz et al [27] - [20] - Results (table 1, fig. 1, 2) There are eleven prospective studies [8,[20][21][22][23][24][25][26][27][28]; Hey man, cited in ref.…”
Section: Studymentioning
confidence: 98%
See 1 more Smart Citation
“…Wade et al [26] _______ ___________ (bilateral carotid occlusion) Fritz et al [27] - [20] - Results (table 1, fig. 1, 2) There are eleven prospective studies [8,[20][21][22][23][24][25][26][27][28]; Hey man, cited in ref.…”
Section: Studymentioning
confidence: 98%
“…In 1985, Fritz et al [27] prospectively evaluated 500 patients with TIA, minor stroke or asymptomatic carotid bruit and found angiographic evidence of ICA occlusion in 32 patients (6.4%). The ICA occlusion was asymptom atic in 3 patients and symptomatic in 29 patients; carotid TIA 17, retinal infarct 1, carotid stroke 11.…”
Section: Prospective Studies O F Patients With Angiographic Evidence mentioning
confidence: 99%
“…After exclusion of patients as described in the Methods section, the 44 studies consisted of 3,457 patients (range 7–714 per study; 2,902 patients with extracranial ICA occlusion, 224 with intracranial ICA stenosis or occlusion, 293 patients with stenosis or occlusion of the MCA, whereas in 38 patients the location of the arterial lesion was not specified), with 12,457 patient-years of follow-up (range 10–3,320 per study). Fifteen studies had a prospective design [1, 4, 5, 6, 9, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20]and 29 were retrospective [3, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48]. Thirty-four studies included patients only if the carotid or MCA lesion had been demonstrated by angiography, whereas in 8 studies the carotid lesion could also be demonstrated by duplex [4, 6, 17, 18, 41, 43, 46, 48]or magnetic resonance angiography [4].…”
Section: Resultsmentioning
confidence: 99%
“…This concept is in direct conflict with the opinion of Gomensoro et al that "when a lesion progressed to complete thrombosis, there was no long er any possibility for emboli to pass into the distal circulation." [18] In the current era of intensive medical therapy, carotid artery disease rarely progresses to occlusion and, when it does, patients' risk of ipsilateral stroke is very low, according to an observational study published online September 21, 2015, ahead of print in JAMA Neurology.…”
Section: Carotid Stenoses and Occlusionsmentioning
confidence: 99%